2013
DOI: 10.1002/dneu.22099
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative transcriptome signature common to neuroblastoma and neural crest cells

Abstract: Neuroblastoma, the most common extracranial tumor in children, is caused by genetic lesions in neural crest precursors of the peripheral nervous system. However, since neural crest cells are neither present after birth and nor are they readily accessible for analysis, very little is known about the genetic networks they might share with neuroblastoma cells during their development, despite their common embryonic origin. Here we have developed a novel resource for lineage tracing and for the isolation of neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Of these, 11 were differentially expressed between MRT subgroups 1 and 2 (FDR < 0.05). 10 of the 11 genes were over-expressed in subgroup 1 (Table S4), including genes linked to neuronal differentiation (e.g., BEX1 , FAM5C/BRINP3; Coyle et al, 2011; Terashima et al, 2010; Vilar et al, 2006) or neural crest differentiation (e.g., ENC1; Rabadán et al, 2013). Conversely, of the 92 genes reported (Grupenmacher et al, 2013) as over-expressed in RTK relative to AT/RT, 21 were differentially expressed between sub-group 1 and 2, and all were over-expressed in sub-group 2 (one-sided Fisher’s exact p value = 1.193e-13; Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 11 were differentially expressed between MRT subgroups 1 and 2 (FDR < 0.05). 10 of the 11 genes were over-expressed in subgroup 1 (Table S4), including genes linked to neuronal differentiation (e.g., BEX1 , FAM5C/BRINP3; Coyle et al, 2011; Terashima et al, 2010; Vilar et al, 2006) or neural crest differentiation (e.g., ENC1; Rabadán et al, 2013). Conversely, of the 92 genes reported (Grupenmacher et al, 2013) as over-expressed in RTK relative to AT/RT, 21 were differentially expressed between sub-group 1 and 2, and all were over-expressed in sub-group 2 (one-sided Fisher’s exact p value = 1.193e-13; Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Besides WE transcriptome analyses, previous genome-wide gene expression studies in vertebrates using low-input RNA sequencing have focused on cleavage, gastrulation, or early organogenesis [ 5 , 7 , 8 , 11 , 79 , 80 ]. At the end of neurulation in particular, transcriptome of definitive NC cells has been obtained just prior to or during their migration [ 81 83 ]. Other studies have taken advantage of naive ectoderm reprogrammed in vitro into different ectoderm cell fates such as neural, NC, or placodes cells [ 10 , 84 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al (2015) showed that metastatic NB was characterized with an increased expression of CD44 marker, compared to non-metastatic controls. Nonetheless, the lack of CD44 expression was associated with aggressive and metastatic behavior, as well as unfavorable outcomes (Munchar et al, 2003; Siapati et al, 2011; Rabadan et al, 2013; Nardella et al, 2015). CD44 is involved in cell-cell adhesion, promoting an antagonistic role vis-a-vis cancer metastasis: its downregulation is thought to be necessary in NB for the cells to acquire a metastatic potential (Rabadan et al, 2013).…”
Section: Bmi1mentioning
confidence: 99%
“…Nonetheless, the lack of CD44 expression was associated with aggressive and metastatic behavior, as well as unfavorable outcomes (Munchar et al, 2003; Siapati et al, 2011; Rabadan et al, 2013; Nardella et al, 2015). CD44 is involved in cell-cell adhesion, promoting an antagonistic role vis-a-vis cancer metastasis: its downregulation is thought to be necessary in NB for the cells to acquire a metastatic potential (Rabadan et al, 2013). This was further supported with retrospective studies showing a correlation between increased expression of CD44 and favorable tumors on histology (Munchar et al, 2003).…”
Section: Bmi1mentioning
confidence: 99%